Refleksi Atas Konsep Peradilan Satu Atap Menuju Pada Tujuan Kekuasaan Kehakiman Yang Mandiri - Fence M. Wantu (JURNAL LEGALITAS, 2009)
Big problems in Indonesian justice since independenced is justice freedom. Many sides wish to influence justice power with various reasoning of importances. Manifestly, there is politics power, economics power, member of society at law direct and or with legal advisor, or even from element of law enfurcer itself. Struggle for towards to one roof judicature as arranged in applied legislation not easy to imagined. Basically, a factor becoming problems to execute of one roof judicature in Indonesia can be grouped into 2 (two) form, that is internal factor and external factor. Kata Kunci: Refleksi, Peradilan Satu Atap, kekuasaan kehakiman, Mandiri